Geochemical Exploration for Heavy Metals in the Stream Sediments of Okemesi-Ijero Area - Ayodele , Olusiji Samuel (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
The bedrocks and gold mineralization have been widely studied especially, in the southern extension of the Ilesha schist belt, but information regarding stream sediments in the area is rarely available in literature. The present study therefore, focused on stream sediments geochemical survey of Okemesi/Ijero axis within the northern extension of Ilesha schist belt using an integrated approach to elucidate the heavy metals potentials and its possible controlling environmental geological conditions. Detailed geological survey involved lithological and structural assessment of the bedrocks. Thirty-five (35) stream sediment samples were collected at a depth of 20-25cm. Major oxides of the stream sediments for major elements were determined using atomic emission spectroscopy (AES). Trace and rare earth elemental analysis was done using inductively coupled plasma mass spectrometry (ICP-MS). Data evaluation was carried out using statistical packages for software simulation. Results showed that bedrock types are quartzbiotite-schists, banded-gneiss, granite-gneiss, biotite-gneiss, calc-gneiss, porphyritic granites, charnockites, massive and schistose quartzites, mica-schists. Structural assessment of the bedrocks revealed folds, fractures and veins as products of Precambrian deformations. Sediments have relatively high concentration of heavy metals such as Mn (387-200ppm), Zn(76.5- 18.52ppm), Pb(39.81-20.23ppm), La 36.2-15.5ppm), Cu(12.68-13.65ppm). However, the folds, fractures and veins provided the groundwork for epigenetic type of mineralization in the studied area.